INNOVATIVE IN SITU TECHNOLOGIES FOR REMEDIATION OF ENERGETICS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The main purpose of the energetic materials is their reactive behavior. All their forms therefore have a footprint on human, animal, and plant systems. The demilitarization operations like Open Burn and Open Detonation, the manufacturing process and the accumulation of disposed munitions create severe contamination of water and soil and that is why it is crucial to understand and influence the caused adverse effects. Managing the munition requires knowledge and great care to avoid public concerns and comply with legislation. The objective for novel “green” energetics in the last years discovers chemical compounds and compositions, which will increasingly be used in munitions. Remediation of the contaminated area can be achieved by employing three main groups of methods: physical, chemical, and biological. Advanced oxidation processes (AOPs) are utilized in applications for which conventional oxidation methods, like chlorination, are insufficient, when process kinetics are slow, or contaminants are resistant to chemical oxidation. In some cases, pollutants become only partially oxidized, resulting in the creation of stable by-products of possibly higher toxicity than the starting substrate. Innovative AOPs using the benefits of combining different methods or utilizing different catalysts to speed up reactions are considered as competitive remediation technics during removal of complex munition pollutants resulting in easy operation and simple preservation in field. AOPs such as Fenton reactions, heterogeneous photocatalysis, Ozonation, and Electrochemical oxidation are effective in removing persistent emerging contaminants that cannot be treated by conventional physicochemical and biological methods. The results show that AOPs could be effective processes for the degradation of explosives. Utilizing in-situ treatment approach for explosive degradation has potential benefits for complete degradation of contaminants, reduced cost and infrastructure compared to traditional methods and reduced overall remediation time.